(untitled) (Comprehensive Journal of Science, 2026)
This research examines the period of the Libyan Kingdom from its independence in 1951 until its fall in 1969, as a pivotal stage in Libya’s modern history. This era began with the declaration of independence under the leadership of King Idris Al-Senussi and the establishment of the first unified Libyan state with a constitutional monarchy. In its early years, the state faced major challenges, including weak infrastructure and heavy reliance on foreign aid. The Kingdom sought to build state institutions and adopted a constitution to regulate political life, establishing a parliamentary system with legislative, executive, and judicial powers. However, political life witnessed significant weakness after the abolition of political parties in 1952, which led to the concentration of power in the hands of the king and the surrounding elite. Economically, Libya experienced a major transformation following the discovery of oil in the late 1950s, which improved revenues and supported development. However, this progress was not accompanied by sufficient institutional reforms, leading to issues such as corruption and regional disparities. Socially, some indicators improved, particularly in education, but challenges such as illiteracy and weak healthcare services persisted. In terms of foreign policy, Libya adopted a moderate approach, leaning toward the West while maintaining Arab and African relations. Over time, opposition increased due to limited political participation and deteriorating social conditions, especially among youth and the military. This ultimately led to a military coup on September 1, 1969, carried out by a group of officers, which ended the monarchy. The research concludes that the fall of the Kingdom was the result of accumulated political, economic, and social factors, despite its achievements in laying the foundations of a modern state.